Expectations of the pediatric intensive care unit team for the clinical pharmacist performance - Andrea Q. Ungari (Medicina, 2016)
Objective: We aimed to know the expectations of a pediatric intensive care unit staff for the activities to be undertaken by the clinical pharmacist, in order to plan her work along with the multidisciplinary team. Study design: A cross-sectional study, involving the multidisciplinary team of the pediatric intensive care unit of a tertiary-care university hospital. Method: A self-completion questionnaire containing questions regarding expectations of the pediatric intensive care unit staff for the role of the clinical pharmacist in the multidisciplinary team was applied to the team members, using a Likert-type scale response. Results: The nursing assistants/technicians and physiotherapists showed higher expectation for issues related to administration of medications; for nurses, the expectation for the clinical pharmacist performance focused on issues related to prescription drugs, such as evaluation of antibiotic therapy, while physicians considered most important information on drug therapy, as notification of allergies related to drugs, information on period of validity of medicines and evaluation of drug administration by gastric or enteral tubes. Conclusions: Team expectations varied according to the needs and routine of each professional category. The results of this study have contributed to implementation of the clinical pharmacy service in a Brazilian pediatric intensive care unit